2016
DOI: 10.1177/0003489416675874
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Quality of Life After Zona Incerta Deep Brain Stimulation

Abstract: Objectives: The management of Parkinson’s disease (PD) has been improved, but management of signs like swallowing problems is still challenging. Deep brain stimulation (DBS) alleviates the cardinal motor symptoms and improves quality of life, but its effect on swallowing is not fully explored. The purpose of this study was to examine self-reported swallowing-specific quality of life before and after caudal zona incerta DBS (cZI DBS) in comparison with a control group. Methods: Nine PD patients (2 women and 7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…There was no clear-cut effect of DBS at 6 and 12 months on any of the swallowing parameters except for the pre-swallow spillage, which was slightly worse in the ON stimulation state 12 months after DBS, although the medication was cut down by one-third post-operatively. Sundstedt et al found no significant difference in SWAL-QOL score and VA scale score 12 months after the DBS at ON medication state in nine PD patients with bilateral cZi ( 23 ). Sundstedt et al also did a prospective longitudinal study on 14 PD patients with bilateral cZi, extending their previous report on swallowing function, before and after DBS at ON medications and ON DBS vs. OFF DBS state by FEES ( 24 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There was no clear-cut effect of DBS at 6 and 12 months on any of the swallowing parameters except for the pre-swallow spillage, which was slightly worse in the ON stimulation state 12 months after DBS, although the medication was cut down by one-third post-operatively. Sundstedt et al found no significant difference in SWAL-QOL score and VA scale score 12 months after the DBS at ON medication state in nine PD patients with bilateral cZi ( 23 ). Sundstedt et al also did a prospective longitudinal study on 14 PD patients with bilateral cZi, extending their previous report on swallowing function, before and after DBS at ON medications and ON DBS vs. OFF DBS state by FEES ( 24 ).…”
Section: Resultsmentioning
confidence: 97%
“…LFS of STN was found to have beneficial effect on dysphagia compared to HFS in patients with FOG refractory to usual HFS of STN (16,17). DBS targeting the post-subthalamic area and caudal zona incerta (PSA/cZi) was thought to be associated with fewer side effects compared to ventralis intermedius (ViM) or STN (21), including the swallowing function (22)(23)(24). GPi DBS has also been used to treat various dystonia (25)(26)(27)(28), including Meige syndrome (29)(30)(31)(32), and its effect on the swallowing function is also of interest to review compared to that in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies on the effects of DBS on swallowing function are controversial. Twelve studies (3 Class II [48][49][50], 9 Class IV [51][52][53][54][55][56][57][58][59]) were retrieved from literature search. In the majority of the studies, DBS targeted the bilateral STN and was delivered with high frequency stimulation.…”
Section: Tablementioning
confidence: 99%
“…In the majority of the studies, DBS targeted the bilateral STN and was delivered with high frequency stimulation. Two studies compared the stimulation of the STN with the stimulation of the GPi [48,55], while one study targeted the caudal zona incerta [57]. Another study compared bilateral stimulation in STN with the combined stimulation of STN and substantia nigra [50].…”
Section: Tablementioning
confidence: 99%
“…While STN-DBS has beneficial effects on pitch variability and range, cZI-DBS displayed no such benefit in a small study of 16 patients with 1-year follow-up [98]. The effect of cZI-DBS on swallowing dysfunction has also been evaluated in 2 longitudinal, prospective studies of 8 and 9 patients [99, 100]. Both studies demonstrated that cZI-DBS did not have a clinically significant impact on either swallowing function or self-reported swallowing-specific quality of life at 1 year postoperatively.…”
Section: New and Emerging Dbs Targets For Refractory Motor Symptomsmentioning
confidence: 99%